1995
DOI: 10.2337/diabetes.44.10.1218
|View full text |Cite
|
Sign up to set email alerts
|

Levels of lipoprotein(a), apolipoprotein B, and lipoprotein cholesterol distribution in IDDM. Results from follow-up in the Diabetes Control and Complications Trial

Abstract: Levels of lipoprotein (a) [Lp(a)], apolipoprotein (apo) B, and lipoprotein cholesterol distribution using density-gradient ultracentrifugation were measured as part of a cross-sectional study at the final follow-up examination (mean 6.2 years) in the Diabetes Control and Complications Trial. Compared with the subjects in the conventionally treated group (n = 680), those subjects receiving intensive diabetes therapy (n = 667) had a lower level of Lp(a) (Caucasian subjects only, median 10.7 vs. 12.5 mg/dl, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 48 publications
(107 reference statements)
2
9
0
Order By: Relevance
“…insulin dose and LDL cholesterol levels are probably more complex. As previously reported, during the DCCT, participants assigned to intensive therapy showed a 34% reduction in LDL cholesterol levels, lower apolipoprotein B, lower cholesterol content of dense LDL and VLDL, and higher content of buoyant LDL compared with subjects in the conventional treatment group (25,26). These findings are consistent with data from metabolic studies in humans showing decreased levels of VLDL triglycerides and LDL cholesterol and increased HDL2 cholesterol levels, along with upregulation of adipose tissue lipoprotein lipase, following insulin therapy (27)(28)(29).…”
Section: Discussionsupporting
confidence: 56%
“…insulin dose and LDL cholesterol levels are probably more complex. As previously reported, during the DCCT, participants assigned to intensive therapy showed a 34% reduction in LDL cholesterol levels, lower apolipoprotein B, lower cholesterol content of dense LDL and VLDL, and higher content of buoyant LDL compared with subjects in the conventional treatment group (25,26). These findings are consistent with data from metabolic studies in humans showing decreased levels of VLDL triglycerides and LDL cholesterol and increased HDL2 cholesterol levels, along with upregulation of adipose tissue lipoprotein lipase, following insulin therapy (27)(28)(29).…”
Section: Discussionsupporting
confidence: 56%
“…This result is reassuring and consistent with reports from other centers with smaller series of patients (9)(10)(11). Furthermore, it is typical of the response one would expect to see with an improvement in glucose control in patients with type 1 diabetes (12). Cyclosporine was associated with a greater reduction in total cholesterol when compared with tacrolimus and mycophenolate, but there was no difference in serum TG between the two groups.…”
Section: Discussionsupporting
confidence: 89%
“…However, most of the latter studies have been cross‐sectional and only the short‐term ( ≤ 6 months) effect of improved glycaemic control on Lp(a) levels have been investigated. Recently, the Diabetes Control and Complications Trial demonstrated that Lp(a) levels were lower in the intensively treated patients with Type 1 diabetes mellitus compared with those in patients receiving conventional therapy[13]. The present study is a long‐term prospective study on the relationship between Lp(a) levels and glycaemic control in Korean patients with Type 2 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 89%